2014
DOI: 10.1136/vr.102431
|View full text |Cite
|
Sign up to set email alerts
|

Feline hyperthyroidism reported in primary‐care veterinary practices in England: prevalence, associated factors and spatial distribution

Abstract: Feline hyperthyroidism is a commonly diagnosed endocrinopathy that can have a substantial deleterious impact on the welfare of affected cats. This study aimed to estimate the prevalence, associated factors and geographical distribution for feline hyperthyroidism in England, using primary-care veterinary practice clinical data from the VetCompass Animal Surveillance Project. Prevalence was estimated from the overall cat cohort. Associated factor analysis used an age-matched, nested, case-control design with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
49
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 20 publications
(57 reference statements)
7
49
2
4
Order By: Relevance
“…Consistent with results from a previous study, our results showed the Burmese breed to be most strongly protected against development of hyperthyroidism . The colorpoint coats of Burmese and Siamese cats occur as a result of 2 separate mutations in the tyrosinase gene, with Burmese cats typically having greater ability to produce pigment in skin covering central body regions than the Siamese .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with results from a previous study, our results showed the Burmese breed to be most strongly protected against development of hyperthyroidism . The colorpoint coats of Burmese and Siamese cats occur as a result of 2 separate mutations in the tyrosinase gene, with Burmese cats typically having greater ability to produce pigment in skin covering central body regions than the Siamese .…”
Section: Discussionsupporting
confidence: 91%
“…But why do these mutations occur? In agreement with previous observations (Kass and others 1999, Wakeling and others 2009), the study by Stephens and others (2014) indicates that Burmese, Siamese, Persian and purebred cats overall had lower odds of hyperthyroidism than non-purebred cats. These observations suggest that the occurrence of the mutations in the TSH receptor or the associated G proteins may be influenced by breed-specific genes.…”
supporting
confidence: 92%
“…The study by Stephens and others (2014) also shows that the risk of feline hyperthyroidism increases with age. This may reflect chronic exposure to goitrogens, which increases the risk of genetic mutations in the thyrocytes.…”
mentioning
confidence: 91%
“…These have been analysed to quantify the most common disorders affecting dogs and cats 7,8 and to establish risk factors for several important conditions 9,10 . Excitingly, VetCompass has now been adapted for use in equine practice, providing enormous opportunity for the study of equine health and the generation of robust disease statistics.…”
mentioning
confidence: 99%